2022
DOI: 10.5771/0935-9915-2022-3-356
|View full text |Cite
|
Sign up to set email alerts
|

Unsilenced Employee Voice in South Africa: Social Media Misconduct Dismissals as Evidence of E-Voice

Abstract: Social media has transformed various aspects of daily life, particularly influencing communication and interaction in both physical and digital spaces. The South African employment relationship is no exception. Social media also creates opportunities for the articulation of employee voice. Through the content analysis of 118 South African first-instance social media misconduct dismissal decisions, this paper argues that employees use social media as a mechanism to express dissenting employee voice. There is ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Whilst recent research by Cornish (2022) in the South African context showed that employees used external SM (such as Facebook and WhatsApp) to express dis-sent despite disciplinary action (dismissals), we argue that anonymity could provide an additional safety measure for employees who refrain from voicing on SM due to fear of negative consequences. Since anonymity provides safety through concealing the identity of the voicer, it allows employees to express themselves without fear of being alienated or labelled a trouble-maker (Milliken et al, 2003).…”
Section: Perceived Safety To Voice Versus Low Privacymentioning
confidence: 63%
“…Whilst recent research by Cornish (2022) in the South African context showed that employees used external SM (such as Facebook and WhatsApp) to express dis-sent despite disciplinary action (dismissals), we argue that anonymity could provide an additional safety measure for employees who refrain from voicing on SM due to fear of negative consequences. Since anonymity provides safety through concealing the identity of the voicer, it allows employees to express themselves without fear of being alienated or labelled a trouble-maker (Milliken et al, 2003).…”
Section: Perceived Safety To Voice Versus Low Privacymentioning
confidence: 63%